Observation of droplet/liquid film impingement between different kinds of liquid simulating fuel spray collision on engine cylinder wall - Shinya OKAMOTO; Hisanobu KAWASHIMA; Ryo UCHIDA; Daisuke TANAKA; Tsuneaki ISHIMA (Nihon Kikai Gakkai ronbunshu, 2021)
Droplet impingement to wet wall is observed and classified. The wet wall has a thin liquid film which is different kind of liquid from the droplets. The present study models the droplets impingements to wet engine walls in gasoline engine. The alternative fuel droplets injected by the injector for port injection system impinge to the silicon oil film simulating wet cylinder wall of actual gasoline engine. In this experiment, a rectangular flow section is used as an example of collision between different liquids in a port injection engine. The viscosity of the liquid film was varied as experimental parameter. The experimental results are well organized using Weber number calculated by using vertical velocity. As Weber number increases, the impingement type changes from rebound to deposit then splash. The tendency is same as impingement regime under the case of same liquid for wet wall and droplets, however critical Weber number is different from them. The liquid film viscosity strongly affects the droplet impingement form. Splash does not occur under the large liquid film viscosity. It is difficult to categorize the impingement regime by common Laplace number based on droplet viscosity. The modified Laplace number which is based on the viscosity of the liquid film is proposed. In the case of different kinds of liquids droplet-film impingement, the phenomenon can be categorized by modified Laplace number and Weber number based on the vertical velocity component of droplet velocity.